Enhancing cryopreservation of organoids via diffusion kinetics analysis using Cryo-Raman microspectroscopy - Altmaier, Saskia; Stracke, Frank; Meiser, Ina; Neubauer, Julia; Zimmermann, Heiko (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):236